PENGARUH PENGETAHUAN PETANI TENTANG MULTIFUNGSI LAHAN SAWAH TERHADAP KEINGINAN PETANI MEMPERTAHANKAN KEPEMILIKAN LAHAN SAWAH DI KORIDOR YOGYAKARTA-MAGELANG - , YUSUF ISKANDAR ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The development of Yogyakarta and Magelang City has had a huge impact on transformation of the area in Yogyakarta-Magelang Corridor. Along the road between Yogyakarta and Magelang has a lot going on land conversion of agricultural land to non-agricultural land. This research aim to know the level of farmers' knowledge about multifunction of paddy field, to know the desire of farmers to retain ownership of paddy fields, to identify the factors that affect farmers' knowledge about multifunction of paddy field and the desire of farmers to maintain paddy fields also to know the effect of farmers' knowledge on multifunction of paddy field toward farmer wishes to maintain the ownership of paddy field. The basic method of this study is survey and using the questionnaire. The number of samples is done proportionally, while making respondents conducted randomly. The analysis used is frequencies table analysis for the first and second purpose, ordinal regression analysis for the third and fourth purpose, and simple linear regression analysis for the last purpose The results showed that the level of farmer knowledge about multifunction of paddy field in general is moderate (51.8 %). The level of farmersâ willing to maintain ownership of paddy field in general is moderate (50 %). Factors that affect the level of farmers' knowledge about multifunction of paddy field is farmers' income from farming, frequency of agricultural extension, education of farmers, farmers main reason for farming, and participation of farmers in farmer groups. Factors that influence the willingness of farmers to maintain ownership of paddy fields were age, education of farmers, wetland distance from the city of Yogyakarta and Magelang, frequency of farmers to follow agricultural extension, and participation in a group of farmers. The influence of farmers' knowledge about multifunction of paddy field toward farmers willing to retain ownership of fields is low (29.6 %).